2009
DOI: 10.1002/arch.20320
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling during early response to injury and microbial challenges in the silkworm, Bombyx mori

Abstract: To identify Bombyx mori genes involved in the early response to injury and microbial challenge, we performed genome-wide gene expression-profiling experiments using oligonucleotide DNA microarrays. Of approximately 23,000 genes examined, 465 displayed changes in mRNA expression levels. Of these, 306 were induced and 159 were repressed in response to injury (injection with phosphate buffer saline) or challenges by Gram-negative (Serratia marcescens), Gram-positive bacteria (Staphylococcus aureus), or fungus (Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…This indicated that ecdysone could efficiently influence the immune system of the silkworm. Similar to other insects, silkworm also contains Toll and IMD signaling pathways to stimulate the expressions of different AMP genes, such as cecropin, gloverin, and moricin, although it is still unclear which AMPs are specifically regulated by which pathway (many AMPs can be upregulated by both positive and negative bacteria) (39)(40)(41). To assess the effect of 20E on silkworm innate immunity, we surveyed the transcriptional responses of several immune-related genes, including AMP genes (Gloverin and Morcin), adaptor of the Toll receptor (Myd88), peptidoglycan recognition protein (PGRP-S6), and cellular immune-related gene (C-type lectin).…”
Section: Effects Of 20e On Silkworm Immunitymentioning
confidence: 99%
“…This indicated that ecdysone could efficiently influence the immune system of the silkworm. Similar to other insects, silkworm also contains Toll and IMD signaling pathways to stimulate the expressions of different AMP genes, such as cecropin, gloverin, and moricin, although it is still unclear which AMPs are specifically regulated by which pathway (many AMPs can be upregulated by both positive and negative bacteria) (39)(40)(41). To assess the effect of 20E on silkworm innate immunity, we surveyed the transcriptional responses of several immune-related genes, including AMP genes (Gloverin and Morcin), adaptor of the Toll receptor (Myd88), peptidoglycan recognition protein (PGRP-S6), and cellular immune-related gene (C-type lectin).…”
Section: Effects Of 20e On Silkworm Immunitymentioning
confidence: 99%
“…This highly diverse taxonomic group of insects encompasses some of the world's most destructive pests in agriculture, as well as many beneficial insects. B. mori, a model system for Lepidoptera, has contributed enormously to the study of Lepidopteran genetics and immunology (Goldsmith et al, 2005;Li et al, 2005Li et al, , 2007Liu et al, 2009;Wu et al, 2010). B. bassiana is one of the major fungal pathogens for silkworms and causes enormous damages to the sericultural industry.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies on the immune systems of other insect species, such as Lepidoptera , contributed to our understanding of the processes and uncovered the differences in their host defense strategies [8,9]. …”
Section: Introductionmentioning
confidence: 99%